Trust and Fertility Intentions in High-Trust Sweden: An Exploratory Analysis - Mark Gortfelder; Gerda Neyer; Gunnar Andersson (Comparative Population Studies, 2024)
Trust has recently received some attention in demographic literature as one potential factor for fertility considerations in post-industrial societies. It has been argued that trust is relevant in a number of different ways, including as a resilience mechanism against different perceived uncertainties that may affect childrearing decisions. Trust is also related to a host of positive political and economic outcomes, all of which enable childbearing. To date, studies have used macro-level or multilevel frameworks and a measure of social trust that focuses on confidence in fellow members of society. In our study, we use two novel modules of the Swedish Generations and Gender Survey 2021 (GGS2021) to study this relationship further. First, we analyse the associations between different measures of interpersonal and institutional trust on the one hand and individuals’ fertility intentions on the other. Second, we examine whether either interpersonal or institutional trust acts as a resilience mechanism against various individual and global uncertainties. The results do not show trust to be a decisive factor behind fertility intentions in Sweden. The absence of strong associations may be attributable to Sweden’s position as a notably high-trust society, with its inclusive labour markets and welfare services.